Validity and reliability of the acceleration-speed profile for assessing running kinematics' variables derived from the force-velocity profile in professional soccer players - Alonso-Callejo, A.; García-Unanue, J.; Guitart-Trench, M.; Majano, C.; Gallardo, L.; Felipe, J. L. (The Journal of Strength and Conditioning Research, 2024)
The aim of this research is to assess the validity and reliability of the acceleration-speed profile (ASP) for measuring the mechanical variables of running kinematics when compared with the force-velocity profile (FVP) obtained by reference systems. The ASP and FVP of 14 male players of an elite football club were assessed during a competitive microcycle. Three ASPs were tested according to the number and type of sessions included in its plotting (ASP1: 5 training sessions and competitive match; ASP2: 5 training sessions; ASP3: competitive match). Force-velocity profile was tested 4 days before match (MD-4) with a 30-m linear sprint using 3 previously validated devices (encoder, mobile App, and global positioning system). Level of significance was p < 0.05. Acceptable reliability (intraclass correlation coefficient > 0.5) was found between the ASP1 and the encoder for all variables (F0-A0, V0-S0, and Vmax). The more reliable ASP method was the ASP1 showing a lower bias than the ASP2 and ASP3 methods for almost all variables and reference systems. For ASP1, lower mean absolute error (MAE: 0.3-0.5) and higher correlation (P-M corr: 0.57-0.92) were found on variables related to the velocity in comparison with variables related to the early acceleration phase (F0-A0; MAE: 0.49-0.63; P-M corr: 0.13-0.41). Acceleration-speed profile, when computed with data from a complete competitive week, is a reliable method for analyzing variables derived from velocity and acceleration kinematics. From these results, practitioners could implement ASP and the applications of the FVP previously studied, such as resistance training prescription, performance assessment, and return-to-play management.